The Role of Nurses in Disaster Management in Asia Pacific - Bonito, Sheila; Minami, Hiroko (Springer International Publishing : Imprint: Springer, 2017)
This book documents how nurses have shown their dedication, courage, expertise and compassion in helping communities prepare for, respond to and recover from disastrous events. It aims to inspire and equip nurses and other health professionals to help people in disaster-affected areas and contribute to community resilience. The last decade (2005-2015) has been characterized by a number of overwhelming natural disasters - tropical storms, floods, earthquakes, tsunamis; and threats of emerging infectious diseases - SARS, MERSCoV and Ebola around the world. Countries from the Asia Pacific region, such as Australia, Cambodia, China, Indonesia, India, Japan, Nepal, Philippines, Solomon Islands, South Korea, Thailand and Vanuatu, have borne the brunt of the devastation caused by these catastrophic events. Nurses from these countries have stepped in providing emergency care in hospitals and in the field, addressing public health needs in evacuation centers, supporting epidemiologic su rveillance and conducting health education, training and research, to help save lives and support communities build back better.
Keywords: Medicine.; Emergency medicine.; Public health.; Critical care medicine.; Primary care (Medicine).; Practice of medicine.; elektronické knihy; electronic books